Análise cinético-funcional comparativa no procedimento de exodontia via fórceps convencional (utilizando empunhadura reversa) e ergofórceps - Garcia, Luciane Tomasi Dalmolin (2013)
Ergonomics applied to the dental activity aims to rationalize the procedures, avoiding unnecessary fatigue to the professional, while still offering safety and comfort to the patient. The extraction, among the several surgical procedures, is considered to cause increased wear and fatigue. To minimize these difficulties, Pece and Naressi (1995) developed a systematic and differentiated extraction technique and the corresponding instrument, a forceps named Ergoforceps. This study aims to compare kinetically and functionally the activity of extraction with the conventional forceps and the ergonomic forceps. For this research, twenty volunteers from the dentistry course of UFPR were analyzed during the activity of alveolar extraction. Photographic images and footage formed the basis for the application of RULA and MOORE GARG (Strain Index) tools. A questionnaire was also applied to the volunteers. These ergonomic analysis tools were selected since they were considered the most suitable to assess the effort made by the upper limbs. The grip used with the conventional forceps was the reverse, which has biomechanical advantages over the traditional. The results obtained with the RULA method for the extraction forceps were: 70% score 5 (moderate risk) and 30% score 6 (moderate risk). In contrast, when the Ergoforceps was used: 70% score 4 (low risk) and 30% score 3 (low risk). With the Moore Garg tool, the score of the volunteers when using the extraction forceps were: 30% score 3 (doubtful) and 70% score 4.5 (doubtful). In contrast, when the Ergofórceps was used the score was: 90% score 1 (low risk) and 10% score 2 (low risk). The results suggest that systematic extraction undergone with the Ergoforceps has ergonomic advantages and reduces the risk of developing occupational injuries among dentists.